Academic Writing Referencing Styles: The Challenges Of An Islamic Law Researcher - Aliyu Aliyu Imam (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2025)
The University of Ilorin Law Referencing Style (UNILARS) is adopted for postgraduate researchers as guide for referencing in academic writings. This also include Islamic law researches. The guide has been in place for more than a decade. Student researchers have always struggled to comply with the obvious requirement of the guidelines, despite its various discrepancies and ambiguous provisions. In the case of Islamic Law researchers, it became more perplexed adopting UNILARS due to the wide vacuum existing in the guidelines regarding Islamic law literature and their unique features in the manner of its presentation; writing names, dates, title of literature, correct manner of referencing Qur‘ān and Hadīth etc. Although, the identified lacuna is not peculiar to UNILARS alone, various other referencing styles also fall short of the recognition. Unity of style in referencing Islamic law literature could however not be achieved, despite adopting a referencing style. These have one way or the other, contribute to the challenges of adopting UNILARS and some other referencing styles in academic writings. This research therefore identified some of the challenges embedded in adopting UNILARS, through doctrinal cum non-doctrinal but qualitative research methodology. The research found and highlights some of the uniqueness of Islamic Law literature which are paramount for consideration in styling any referencing guide. A model referencing style is therefore proposed for Islamic law researchers named: University of Ilorin Shari‘ah Law Referencing Style (UNISLARS) to curb the challenges.